Precarious Imaginaries of Beirut A City's Suspended Now - Naeff, Judith (Springer International Publishing, 2018)
This book investigates a shared experience of time and space in the post-civil-war city of Beirut: "the suspended now". Based on the close analysis of a large corpus of cultural objects; including visual art, literature, architecture and cinema; the book argues that last decades have witnessed a gradual shift in understanding this temporality from being a transitional phase to a more durable experience of precariousness. The theoretically rich analyses take us on a journey through Beirut's real and imagined geographies, from garbage dumps to real estate advertisements, and from subterranean spaces to martyr's posters. For scholars of cultural analysis, urban studies, cultural geography and critical theory, the case of post-1990 Beirut offers a fascinating case of neoliberal urban renewal, which challenges existing theories. For scholars of Lebanon and Beirut, this study complements existing work on post-civil-war Lebanese cultural production rooted in trauma studies by its focus on the city's continual exposure to violence.